Accuracy of Guided Implant Surgery Using Tooth-Supported Surgical Guide for Immediate Versus Late Implant Placement: A Retrospective Clinical Study - Ko, Kang Hoon. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Posthodontics.; Advisor: André de Souza.; Committee: Matthew Finkelman, Yong Jeong Kim, Panos Papaspyridakos, and Khaled El-Rafie.; Keyword: Dentistry.